Analysis of the Influence of the Company's Internal Environment and the External Environment of the Company on Accountant Professional Code of Conduct - Sulvia Trifatmala (Journal of Contemporary Information Technology, Management, and Accounting, 2022)
This study aims to determine the effect of the company's internal environment and the company's external environment on the code of ethics for the accountant profession. The research problems are as follows: Does the company's internal environment and the company's external environment affect the code of ethics for the accountant profession? The purpose of this study is to determine whether the company's internal environment and the external environment of the company affect the code of ethics for the accountant profession. This study examined 35 respondents by giving them a questionnaire before collecting data. The analytical method used is multiple linear regression statistical analysis and uses the T test to analyze the closeness of the relationship between individual variables, while testing the instrument using validity and reliability tests. The results of the analysis show that the company's internal environment and the company's external environment have no positive effect on the code of ethics for the accounting profession.